Edukasi Gizi Bayi Berbasis Pangan Lokal pada Ibu Menyusui - Wida Rahma Arwiyantasari; Rury Narulita Sari; Siti Nur Fadillah (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
In the health sector, the government plans to reduce stunting rates by 40% in 2025. This goal has been stated in the Infant and Young Child Feeding (IYCA) program. In practice, mothers make mistakes in feeding their children influencing the nutritional status of the children resulting in an inability to fulfill the child’s nutrition needs. This condition occurred due to a lack of knowledge and information during the IYCF period. This study aims to provide knowledge to mothers about the importance of complementary feeding made from local food ingredients. This case study analyzed the growth development and nutritional status of an 11-month-old baby. Subjective examination showed that the mother felt that her baby's nutritional status was lacking so she came to the clinic to have her baby checked. Objective examinations of the baby's weight and height were performed. The mother received local food-based nutritional counseling. Midwives provided education about the importance of complementary feeding made from local food ingredients and provided support to mothers to continue breastfeeding their babies. The midwives also provided cooking recipes and nutritional content of food made from local food ingredients to the mother so she could independently practice it.